Über grosse Abweichung für diskreten Zufallsgrößen - Survila, P. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:П. Сурвила. О больших уклонениях в локальной теореме для решетчатых случайных величинP. Survila. Apie didelius nukrypimus lokalinėje teoremoje rėtiniams dydžiams